Paediatric astroblastoma‐like neuroepithelial tumour of the spinal cord with a MAMLD1‐BEND2 rearrangement. (10th April 2022) - Rossi, Sabrina; Barresi, Sabina; Colafati, Giovanna Stefania; Giovannoni, Isabella; Miele, Evelina; Alesi, Viola; Cacchione, Antonella; Diomedi‐Camassei, Francesca; Macari, Gabriele; Antonelli, Manila; Carboni, Alessia; Carai, Andrea; et al.
Abstract: Astroblastomas are neuroepithelial tumours defined by the presence of MN1 rearrangement and are typically located in the cerebral hemispheres. Rare cases of astroblastoma‐like tumours carrying an EWSR1‐BEND2 fusion have been recently described in the brain stem and spinal cord. We report a paediatric case of neuroepithelial astroblastoma‐like tumour occurring in the spine and carrying a novel MAMLD1‐BEND2 fusion. We believe that our case aligns with the rare astroblastoma‐like tumours with EWSR1‐BEND2 fusion, in terms of non‐hemispheric location, pathology, methylation profile and activation of BEND2 transcription. Whether they may represent a distinct entity or a variant of MN1 ‐altered astroblastoma is not clear.